NATO's push into the Caucasus: geopolitical flashpoints and limits for expansion. Issue 4 (2nd October 2017) - Antonopoulos, Paul; Velez, Renato; Cottle, Drew
ABSTRACT: The Caucasus has been a major flashpoint of contention between NATO and a resurgent Russia since the collapse of the Soviet Union. The rivalry saw the escalation of hostility in the region during the brief 2008 Russo-Georgian War where a NATO-backed Georgia challenged South Ossetia supported by the Russian military. In 2011, NATO officially recognised Georgia as a potential member, challenging Russia's traditional sphere of influence in the Caucasus. Moscow says the Eastward expansion of NATO into the Baltics and to include Georgia as a member state is a method of containing a resurgent Russia. However, the former Soviet Republics of Ukraine, the Baltics and Georgia, maintain that Russia represents a threat to their sovereignty, as seen by the Russian support of the breakaway unrecognised Republics of South Ossetia and Abkhazia. A hostile rivalry between the Russian-backed Armenia and Azerbaijan, which is reliant upon NATO-member Turkey, intensifies the polarisation in the Caucasus.